Non-labile silver species in biosolids remain stable throughout 50 years of weathering and ageing. (October 2015) - Donner, E.; Scheckel, K.; Sekine, R.; Popelka-Filcoff, R.S.; Bennett, J.W.; Brunetti, G.; Naidu, R.; McGrath, S.P.; Lombi, E.
Abstract: Increasing commercial use of nanosilver has focussed attention on the fate of silver (Ag) in the wastewater release pathway. This paper reports the speciation and lability of Ag in archived, stockpiled, and contemporary biosolids from the UK, USA and Australia, and indicates that biosolids Ag concentrations have decreased significantly over recent decades. XANES revealed the importance of reduced-sulfur binding environments for Ag speciation in materials ranging from freshly produced sludge to biosolids weathered under ambient environmental conditions for more than 50 years. Isotopic dilution with 110m Ag showed that Ag was predominantly non-labile in both fresh and aged biosolids (13.7% mean lability), with E-values ranging from 0.3 to 60 mg/kg and 5 mM CaNO3 extractable Ag from 1.2 to 609 μg/kg (0.002–3.4% of the total Ag). This study indicates that at the time of soil application, biosolids Ag will be predominantly Ag-sulfides and characterised by low isotopic lability. Highlights: Biosolids silver (Ag) concentrations appear to have decreased in recent decades. Ag2 S dominates Ag speciation in freshly produced sludge. Ag2 S is also the dominant species in aged biosolids. Upon land application biosolids will mainly contain Ag-sulfides and have low isotopic lability. Abstract : Analysis of historic and contemporary biosolids from three continents indicated decreasing wastewater silver releases, and non-labile, extremely stable silver speciation.